2008
DOI: 10.1176/appi.ajp.2008.08050756
|View full text |Cite|
|
Sign up to set email alerts
|

Double-Blind Comparison of First- and Second-Generation Antipsychotics in Early-Onset Schizophrenia and Schizo-affective Disorder: Findings From the Treatment of Early-Onset Schizophrenia Spectrum Disorders (TEOSS) Study

Abstract: Risperidone and olanzapine did not demonstrate superior efficacy over molindone for treating early-onset schizophrenia and schizoaffective disorder. Adverse effects were frequent but differed among medications. The results question the nearly exclusive use of second-generation antipsychotics to treat early-onset schizophrenia and schizoaffective disorder. The safety findings related to weight gain and metabolic problems raise important public health concerns, given the widespread use of second-generation antip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
266
3
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 417 publications
(293 citation statements)
references
References 44 publications
10
266
3
10
Order By: Relevance
“…Acute TEOSS data found that olanzapine and risperidone were associated with significant weight gain, and olanzapine was associated with lipid and liver function changes. 3 However, those analyses included subjects that discontinued after participation in the acute study due to metabolic side effects, whereas these maintenance data include only those that tolerated acute treatment and continued in this trial. Therefore, there is a selection bias towards patients that did not develop clinically significant adverse events during acute therapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Acute TEOSS data found that olanzapine and risperidone were associated with significant weight gain, and olanzapine was associated with lipid and liver function changes. 3 However, those analyses included subjects that discontinued after participation in the acute study due to metabolic side effects, whereas these maintenance data include only those that tolerated acute treatment and continued in this trial. Therefore, there is a selection bias towards patients that did not develop clinically significant adverse events during acute therapy.…”
Section: Discussionmentioning
confidence: 99%
“…3,5 In this report we focus on the 44-week, double-blind extension phase that followed the 8-week, double-blind acute trial. The primary results of the acute study have been described previously.…”
Section: Methods Study Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Low-density lipoprotein and triglyceride levels were reported to increase in both groups [35]. In contrast to these findings, another study involving a different patient group observed a small increase in HDL levels in patients receiving olanzapine after 8 weeks' treatment, while a decrease was observed in HDL levels in patients treated with risperidone [36].…”
Section: Discussionmentioning
confidence: 82%